Georg Busolt : his career in his letters - Busolt, Georg, 1850-1920. (Mnemosyne, Supplements, 1990)
This book is a study of Georg Busolt (1850-1920), a noted German historian of classical Greece. The treatment is based on a collection of his own letters, mainly written to other scholars. Over 100 letters from Busolt to others are collected and edited here. Each letter, in the original German, is presented with commentary and the whole is woven into a chronological narrative and survey of Busolt's career. There are four chapters (The Busolt Family; Königsberg; Kiel, Göttingen), the last three corresponding to the universities where he studied and taught. Despite Busolt's eminence and the continued usefulness of his two great handbooks ( Griechische Geschichte; Griechische Staatskunde ), nothing has ever been written about him. Moreover, the narrative gives a picture of Prussian universities and academic issues during his period - a crucial one for the development of German education - and is thus a contribution to the history of scholarship.